2016
DOI: 10.2355/isijinternational.isijint-2015-492
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Effect of Slag Thickness on Metal Pool Profile in Electroslag Remelting Process

Abstract: A transient three-dimensional (3D) model was developed to understand the role slag thickness plays in the formation of the metal pool in the electroslag remelting (ESR) process. In this model, the solution of the mass, momentum and energy conservation equations were simultaneously implemented by the finite volume method with full coupling of the Joule heating and Lorentz force by solving the Maxwell's equations. The movement of metal droplet was described by volume of fluid (VOF) approach. Additionally, the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…15,16) Kharicha et al solved the electromagnetic field with electric potential method coupled with a VOF model to track the motion of metal droplets and phase boundaries, and concluded that the highest magnetic field intensity appears at the surface of droplets. 17) Wang et al developed a laboratory scale 3D multiphase-magneto-hydrodynamic model considering the effect of metal droplets on electromagnetic field, [18][19][20][21] and studied the multiphase flow and solidification in ESR process. Glesselmann et al studied the movement of droplets and solidification process using coupled multi zone models, which were solved with different time steps.…”
Section: Effects Of Metal Droplets On Electromagnetic Field Fluid Flmentioning
confidence: 99%
“…15,16) Kharicha et al solved the electromagnetic field with electric potential method coupled with a VOF model to track the motion of metal droplets and phase boundaries, and concluded that the highest magnetic field intensity appears at the surface of droplets. 17) Wang et al developed a laboratory scale 3D multiphase-magneto-hydrodynamic model considering the effect of metal droplets on electromagnetic field, [18][19][20][21] and studied the multiphase flow and solidification in ESR process. Glesselmann et al studied the movement of droplets and solidification process using coupled multi zone models, which were solved with different time steps.…”
Section: Effects Of Metal Droplets On Electromagnetic Field Fluid Flmentioning
confidence: 99%
“…[30] Moreover, it has been suggested that the metal pool profile decides the macrosegregation contour in the ESR ingot. [31] Therefore, the effect of slag thickness on the metal pool profile should be studied thoroughly. Figure 14 provides maximum depth of metal pool and temperature in relation to different slag thicknesses.…”
Section: F Effect Of Slag Thicknessmentioning
confidence: 99%
“…The effect of electrode immersion depth, power control function, slag thickness, solidified slag, and current on multi-physical fields are also discussed. [33][34][35][36][37] Dong et al [38,39] investigated a novel singlepower two-circuit ESR process (ESR-STCCM) with currentcarrying mold via numerical simulation and experimental research. A 2D quasi-steady-state mathematical model was established to describe ESR-STCCM.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al developed a transient 3D coupled mathematical model to explore electromagnetic phenomena, flow, and temperature fields, solidification, inclusion motion behavior, desulfurization and oxygen transfer in the ESR process. The effect of electrode immersion depth, power control function, slag thickness, solidified slag, and current on multi‐physical fields are also discussed . Dong et al investigated a novel single‐power two‐circuit ESR process (ESR‐STCCM) with current‐carrying mold via numerical simulation and experimental research.…”
Section: Introductionmentioning
confidence: 99%